Knowledge of PCSK9 and Continued Educational Gaps. Issue 1 (March 2015) - Larkin, Amy T.; Healy, Colleen S.; Toth, Peter P.
<x xml:space="preserve">Abstract</x> Reducing serum levels of low-density lipoprotein–cholesterol (LDL-C) is an important treatment objective in both the primary and secondary prevention settings. Although statin therapy remains the gold standard for reducing LDL-C, for a variety of reasons, many patients taking statins do not achieve adequate cholesterol lowering. This has created a need for new treatment approaches to manage dyslipidemia. One potential emerging treatment option to promote greater LDL-C reduction is the class of proprotein convertase subtilisin/kexin 9 (PCSK9) monoclonal antibodies, currently in phase 3 development. This study evaluated the impact of continuing medical education (CME) on increasing knowledge and awareness of the role of PCSK9 in lipid metabolism and analyzed persistent educational gaps to determine needs for future education. For cardiologists who participated in the CME activity, comparison of individually linked preassessment question responses to their respective postassessment question responses demonstrated improvement (n = 83; P < 0.05). Correct responses on postassessment questions ranged between 63% and 253% higher after CME, with an overall effect size of 0.72. Between 24% and 47% of learners showed improvement in understanding individual learning concepts. In the ever-evolving landscape of dyslipidemia management, CME demonstrably impacted knowledge of the PCSK9 monoclonal antibodies.